Methane sources and sinks in continental sedimentary systems: New insights from paired clumped isotopologues 13CH3D and 12CH2D2. (15th January 2019) - Giunta, Thomas; Young, Edward D.; Warr, Oliver; Kohl, Issaku; Ash, Jeanine L.; Martini, Anna; Mundle, Scott O.C.; Rumble, Douglas; Pérez-Rodríguez, Ileana; Wasley, Mark; LaRowe, Douglas E.; Gilbert, Alexis; et al.
Abstract: Stable isotope compositions of methane (δ 13 C and δD) and of short-chain alkanes are commonly used to trace the origin and fate of carbon in the continental crust. In continental sedimentary systems, methane is typically produced through thermogenic cracking of organic matter and/or through microbial methanogenesis. However, secondary processes such as mixing, migration or biodegradation can alter the original isotopic and composition of the gas, making the identification and the quantification of primary sources challenging. The recently resolved methane 'clumped' isotopologues Δ 13 CH3 D and Δ 12 CH2 D2 are unique indicators of whether methane is at thermodynamic isotopic equilibrium or not, thereby providing insights into formation temperatures and/or into kinetic processes controlling methane generation processes, including microbial methanogenesis. In this study, we report the first systematic use of methane Δ 13 CH3 D and Δ 12 CH2 D2 in the context of continental sedimentary basins. We investigated sedimentary formations from the Southwest Ontario and Michigan Basins, where the presence of both microbial and thermogenic methane was previously proposed. Methane from the Silurian strata coexist with highly saline brines, and clumped isotopologues exhibit large offsets from thermodynamic equilibrium, with Δ 12 CH2 D2 values as low as −23‰. Together with conventional δ 13 C and δD values, the variability in Δ 13 CH3 D and Δ 12 CH2 D2 to first order reflects a mixing relationship between near-equilibrated thermogenic methane similar to gases from deeper Cambrian and Middle Ordovician units, and a source characterized by a substantial departure from equilibrium that could be associated with microbial methanogenesis. In contrast, methane from the Devonian-age Antrim Shale, associated with less saline porewaters, reveals Δ 13 CH3 D and Δ 12 CH2 D2 values that are approaching low temperature thermodynamic equilibrium. While microbial methanogenesis remains an important contributor to the methane budget in the Antrim Shale, it is suggested that Anaerobic Oxidation of Methane (AOM) could contribute to reprocessing methane isotopologues, yielding Δ 13 CH3 D and Δ 12 CH2 D2 signatures approaching thermodynamic equilibrium.